High‐Mobility Field‐Effect Transistors Fabricated with Macroscopic Aligned Semiconducting Polymers. (6th February 2014) - Tseng, Hsin‐Rong; Phan, Hung; Luo, Chan; Wang, Ming; Perez, Louis A.; Patel, Shrayesh N.; Ying, Lei; Kramer, Edward J.; Nguyen, Thuc‐Quyen; Bazan, Guillermo C.; Heeger, Alan J.
<x xml:space="preserve">Abstract</x> A record high OFET hole mobility, as high as 23.7 cm2/Vs, is achieved in macroscopic aligned semiconducting polymers. The high mobility is insensitive to the polymer molecular weight. Polymer chains are aligned along the fiber to facilitate intrachain charge transport. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>